The Challenge of the Interpreter in Interpreting Non-native English Speakers: A Case Study - EIT Case at Court of Gianyar â Bali - Ana, I Wayan (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
The aim of this research is to find out the challenges faced by the interpreter in interpreting Bulgarian Accused for the ATM Case. To discuss the problems of this research, eclectic theories are applied. But facial Pochhakers theory is applied as the main theory for interpreting andother theories of syntax, semantics and pragmatics as well as semiotics. The data used for this research were taken from court examination at the District Court of Gianyar in the case of two Bulgarians charged engines with Article 30 paragraph (2) and Article 33 of Law No. 11 of 2008. Based on the result of the analysis, it was found that there are some challenges faced by the interpreter in charge for foreign accused in the District Court, such us, week voice of the accused, poor and unclear features of English, incorrect grammar and limited vocabulary. To cope these difficulties, the strategies applied in interpreting English to English acres paraphrasing with addition and simplification of information, shift of information as well as non-technical strategy, by using hand illustration while to understand their English the interpreter observed the Accused facial expressions and gestures, and noticing the mouths and forms of lips.